Long Non−Coding RNA H19 Regulates Glioma Cell Growth and Metastasis via miR-200a-Mediated CDK6 and ZEB1 Expression - Chen, Xuezhu; Li, Yuhong; Zuo, Chenghai; Zhang, Kaiyuan; Lei, Xuejiao; Wang, Ju; Yang, Yang; Zhang, Jianmin; Ma, Kang; Wang, Shi; Mu, Ning; Yang, Chuanyan; et al. (Frontiers in Oncology, 2021)
Long non-coding RNAs (lncRNAs) serve essential roles on various biological functions. Previous studies have indicated that lncRNAs are involved in the occurrence, growth and infiltration of brain tumors. LncRNA H19 is key regulator in the pathogenesis of gliomas, but the underlying mechanisms of H19-regulated tumor progression remain unknown. Therefore, we investigated the effects and mechanism of action (MOA) of lncRNA H19 on the homeostasis of glioma cells. As a novel oncogenic factor, up-regulation of H19 was able to promote the proliferation of glioma cells by targeting miR-200a. Furthermore, elevated miR-200a levels could reverse H19-induced cell growth and metastasis. Overexpression of miR-200a could significantly suppress the proliferation, migration and invasion of glioma cells. These biological behavior changes in glioma cells were dependent on the binding to potential target genes including CDK6 and ZEB1. CDK6 could promote cell proliferation and its expression was remarkably increased in glioma. In addition, up-regulation of miR-200a lead to reduction of CDK6 expression and inhibit the proliferation of glioma cells. ZEB1 could be a putative target gene of miR-200a in glioma cells. Thus, miR-200a might suppress cell invasion and migration through down-regulating ZEB1. Moreover, overexpression of miR-200a resulted in down-regulation of ZEB1 and further inhibited malignant phenotype of glioma cells. In summary, our findings suggested that the expression of H19 was elevated in glioma, which could promote the growth, invasion and migration of tumor cells via H19/miR-200a/CDK6/ZEB1 axis. This novel signaling pathway may be a promising candidate for the diagnosis and targeted treatment of glioma.